Reconstruction of Chronic Wounds Secondary to Injectable Drug Use with a Biodegradable Temporizing Matrix. Issue 7 (12th July 2021) - Cheng, Christopher; Kwiecien, Grzegorz J.; Rowe, David J.; Gatherwright, James R.; Chepla, Kyle J.
Abstract : Summary: Injectable drug use in the upper extremity often leads to chronic wounds complicated by osteomyelitis. Conventional reconstructive options are often not feasible and/or are contraindicated in this patient population. We have started using a synthetic, biodegradable temporizing matrix (BTM) for the treatment of these patients. We hypothesize that BTM is a safe, low-risk, and low-morbidity alternative reconstructive option. We report outcomes after staged debridement and BTM application followed by split-thickness skin grafting for two patients with large, chronic bilateral forearm wounds with concomitant osteomyelitis confirmed by MRI and biopsy. No acute surgical complications were encountered and at a mean follow-up of 13 months, both patients had maintained stable soft-tissue coverage. Reconstruction using BTM is a novel treatment option that can simplify the reconstruction, reduce donor-site morbidity, and optimize success for patients with chronic wounds resulting from injectable drug use. Initial outcomes are promising; however, further comparative studies are needed to better evaluate long-term outcomes of this technique.